How I met my monster - Stine, R. L. (New York : Scholastic, 2013)
Unpopular Noah Bienstock begins to suspect that there is something odd about his new friend and neighbor.
3.1
3-6.
3-6
Keywords: Friendship -- Juvenile fiction; Monsters -- Juvenile fiction; Popularity -- Juvenile fiction; Friendship -- Fiction; Horror stories; Monsters -- Fiction; Popularity -- Fiction; Friendship -- Fiction; Horror fiction; Monsters -- Fiction; Popularity -- Fiction; Horror fiction